Application of Group Investigation (GI) Learning Model to Improve Biology Cognitive Ability and Cooperation of Class X-10 Students of SMA Negeri 2 Nganjuk - Alifa Mareta Ganes Sabrina; Purwo Adi Nugroho (Magister Pendidikan Sains Universitas Sebelas Maret, 2025)
Tingkat pemahaman siswa terhadap konsep-konsep sains masih tergolong rendah. Hal ini terlihat dari rendahnya hasil belajar siswa dalam aspek kognitif. Penelitian bertujuan untuk menganalisis model Pembelajaran Group Investigation (GI) untuk meningkatkan kemampuan kognitif biologi dan kerja sama siswa. Jenis penelitian adalah tindakan kelas dengan tiap siklus terdiri dari tahap perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian melibatkan 36 siswa kelas X-10. Metode pengumpulan data dengan observasi dan tes. Teknik analisis data menggunakan analisis kuantitatif deskriptif. Hasil penelitian menunjukkan siklus 1 dan 2 hasil belajar menjadi lebih baik siswa pada aspek kognitif sebelum diberi tindakan dan setelah diberi tindakan sebesar 100%, hasil belajar menjadi lebih baik pada aspek psikomotor dan afektif dari siklus I ke siklus II berturut-turut 76% dan 100%. Simpulan penelitian yaitu penerapan model Pembelajaran Group Investigation (GI) dapat meningkatkan kemampuan kognitif biologi dan kerja sama siswa. Implikasi penelitian diharapkan adanya model Pembelajaran Group Investigation (GI) akan dapat mengembangkan kemampuan kerja samanya dan matematisnya karena model ini membantu siswa memecahkan masalah melalui percobaan atau penelitian sederhana.The level of students' understanding of science concepts is still relatively low. This can be seen from the low student learning outcomes in the cognitive aspect. The research aims to analyze the Group Investigation (GI) learning model to improve students' biological cognitive abilities and collaboration. The type of research is classroom action with each cycle consisting of planning, implementation, observation and reflection stages. The research subjects involved 36 students in class X-10. Data collection methods are observation and tests. The data analysis technique uses descriptive quantitative analysis. The results showed that in cycles 1 and 2 students' learning outcomes were better in the cognitive aspect before being given action and after being given action by 100%, learning outcomes were better in the psychomotor and affective aspects from cycle I to cycle II respectively 76% and 100%. The conclusion of the research is that the application of the Group Investigation (GI) learning model can improve students' biological cognitive abilities and collaboration. The research implications are that it is hoped that the Group Investigation (GI) learning model will be able to develop cooperation and mathematical abilities because this model helps students solve problems through simple experiments or research.